Tellurium and niobium doped and carbon nitride coated positive electrode material and preparation method thereof
By using tellurium and niobium doping and carbon nitride coating technology in the positive electrode material, the safety performance and structural stability of nickel-rich positive electrode material are solved, the rate performance and cycle stability of the battery are improved, and the electronic conductivity is enhanced and ion diffusion rate reduce the risk of thermal runaway and improve the overall performance of the battery.
Patent Information
- Application Number
- CN202411446785.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2024-12-24
AI Technical Summary
The existing nickel-rich cathode materials have problems such as reduced safety performance, unstable structure, severe high-temperature inflation, low first-time Coulomb efficiency, and reduced magnification and circulation performance in electric vehicle applications.
The positive electrode material coated with tellurium and niobium doping and carbon nitride coating is adjusted through Te/Nb co-doping and carbon nitride coating, and the energy band structure and charge distribution of the material are increased, electron transport channels are improved, and the adsorption of lithium ions is improved. and desorption capacity, and improve heat conduction properties through carbon nitride coating, reducing surfactivity and structural instability.
It improves the rate performance, reversible capacity, cycle stability and safety performance of the positive electrode material, enhances electronic conductivity and ion diffusion rate, reduces the risk of thermal runaway and battery self-discharge rate, and improves the storage performance and safety of the battery.
Smart Images

Figure CN119181789A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery positive electrode materials, and in particular relates to a tellurium and niobium doped and carbon nitride coated positive electrode material and a preparation method thereof. Background Art
[0002] With the continuous advancement of science and technology, lithium-ion batteries have been widely used in portable electronic devices, electric vehicles, energy storage systems and other fields. In order to solve the main obstacle of limited mileage in the commercialization of electric vehicles, people are developing nickel-rich positive electrode materials. However, nickel-rich positive electrode materials still have some shortcomings in performance, such as chemical and structural instability leading to rapid capacity decay, volume change and phase change during charging and discharging, lattice distortion and collapse, and poor cycle stability.
[0003] As the nickel content increases, the surface activity of the material increases, the heat generated increases, the probability of thermal runaway increases, and the safety performance of the battery decreases; due to the increase in nickel content, the lithium ions migrating on the surface of the active material are very likely to react with the carbonate ions on the surface of the material to form lithium carbonate, and decompose under high pressure, which can easily cause the battery to swell, resulting in structural instability and serious high-temperature swell problems; as the nickel content increases, the Li / Ni mixing becomes serious, and it also makes it easier for transition metal elements to migrate to the lithium layer, which in turn causes the material to transform from a layered structure to a rock salt and spinel structure, making Li + The resistance to migration at the material interface increases, and the loss of irreversible capacity is large, resulting in a low first coulombic efficiency of the material; in a low temperature environment, the electronic conductivity and ion diffusion rate are poor, the interface resistance increases, the lithium ion migration speed is slow, and the rate and cycle performance are reduced. Summary of the invention
[0004] In order to overcome the shortcomings of the above-mentioned prior art, the present invention provides a tellurium and niobium doped and carbon nitride coated positive electrode material and a preparation method thereof, which solves the problems of reduced safety performance, unstable structure and severe high-temperature flatulence, low first coulombic efficiency, and reduced rate and cycle performance of the existing nickel-based positive electrode materials for batteries.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A tellurium and niobium doped and carbon nitride coated cathode material, the chemical formula is: LiNi x Co y Mn 1-x-y-u-v Te u Nb v O2@C3N4;
[0007] Among them, 0.5 ≤ x ≤ 0.98, 0 < y < 0.5, 0 < u ≤ 0.1, 0 < v ≤ 0.1, and 1 - x - y - u - v > 0.
[0008] Furthermore, the tellurium and niobium doped and carbon nitride coated cathode material includes a tellurium and niobium doped cathode material, and carbon nitride coated on the surface of the tellurium and niobium doped cathode material.
[0009] The present invention also discloses a preparation method of the above-mentioned tellurium and niobium doped and carbon nitride coated cathode material, comprising the following steps:
[0010] Step 1: Weigh nickel salt, cobalt salt, manganese salt, tellurium salt and niobium salt according to the stoichiometric ratio in the chemical formula, dissolve them in deionized water, mix and stir to obtain a mixed solution A;
[0011] Step 2: Add a precipitant to the mixed solution A, adjust the pH value of the solution to alkaline, stir and react to obtain a mixed solution B;
[0012] Step 3: Filter the mixed solution B by suction, wash the precipitate, and then vacuum dry at 80 - 120 °C for 12 - 24 hours to obtain a precursor;
[0013] Step 4: Mix the precursor with lithium salt充分, heat up to 600 - 950 °C, keep warm for 8 - 16 hours, naturally cool to room temperature, crush and screen to obtain a tellurium and niobium doped cathode material;
[0014] Step 5: Mix the tellurium and niobium doped cathode material with a nitrogen-containing precursor evenly, under an inert atmosphere, heat up to 400 - 600 °C, keep warm for 2 - 6 hours, naturally cool to room temperature, crush and screen to obtain a tellurium and niobium doped and carbon nitride coated cathode material.
[0015] Furthermore, in Step 1, the rotation speed is controlled at 300 - 500 revolutions per minute;
[0016] The nickel salt is one or more of nickel sulfate, nickel chloride, nickel carbonate, nickel nitrate;
[0017] The cobalt salt is one or more of cobalt sulfate, cobalt chloride, cobalt carbonate, cobalt nitrate;
[0018] The manganese salt is one or more of manganese sulfate, manganese chloride, manganese carbonate, manganese nitrate;
[0019] The tellurium salt is one or more of tellurium sulfate, tellurium chloride, sodium tellurate;
[0020] The niobium salt is one or more of sodium niobate, niobium oxalate, niobium hydroxide.
[0021] Furthermore, in Step 2, the precipitant includes one or more of ammonia water, sodium hydroxide, sodium carbonate;
[0022] The pH value was adjusted to 9-12, and the drop rate of the precipitant was controlled at 1-2 ml / min;
[0023] The stirring speed is 400-600 rpm, and the reaction is stirred for 2-6 hours. During the stirring process, the temperature is maintained at 25-35°C.
[0024] Further, in step 4, the lithium salt is lithium carbonate and / or lithium hydroxide;
[0025] In air or oxygen atmosphere, the temperature is increased to 600-950°C at a heating rate of 5-10°C / min.
[0026] Furthermore, in step 4, the mass ratio of the precursor to the lithium salt is 1:(1.04-1.06).
[0027] Furthermore, in step 5, the mass ratio of the tellurium and niobium doped positive electrode material to the nitrogen-containing precursor is 100:(1-10).
[0028] Furthermore, in step 5, the nitrogen-containing precursor is one or more of melamine, urea, and dicyandiamide.
[0029] Further, in step 5, the inert atmosphere includes one or more of nitrogen, argon, and helium;
[0030] The temperature was raised to 400-600°C at a heating rate of 2-5°C / min.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] The present invention also discloses a tellurium and niobium doped and carbon nitride coated positive electrode material. Nb doping can adjust the energy band structure of the material, increase the electron transmission channel, and reduce the resistance of electron transmission, thereby improving the rate performance of the positive electrode material; Te doping changes the charge distribution of the material and forms more active sites inside the material. These active sites are conducive to the adsorption and desorption of lithium ions and improve the reversible capacity of the positive electrode material; when Te and Nb are co-doped, Nb improves the electronic conductivity and provides a good electronic channel for the transmission of lithium ions, while the active sites increased by Te provide more positions for the storage and reaction of lithium ions. The synergistic modification of Te / Nb effectively enhances the electronic conductivity and ion diffusion rate, so that the material performs better under high rate charge and discharge, and can meet the needs of fast charging and large current discharge.
[0033] Nb doping reduces surface defects and instability of the positive electrode material caused by structural changes during the charge and discharge process, inhibits the formation of lithium carbonate by lithium ions migrating on the surface of the positive electrode material and carbonate ions on the surface of the material, and the Te doped element forms a stronger chemical bond with the oxygen atoms on the surface of the positive electrode material, reducing the combination of oxygen and carbonate ions, thereby hindering the formation of lithium carbonate; Nb forms a stable passivation layer on the surface of the positive electrode material to prevent direct contact between the positive electrode material and the electrolyte, reduce the corrosion of the electrolyte on the positive electrode material, and inhibit the decomposition reaction of the electrolyte on the surface of the positive electrode material, thereby reducing the self-discharge rate of the battery and improving the storage performance of the battery; Te doping changes the surface chemical properties of the positive electrode material, making its surface more resistant to harmful substances in the electrolyte, and reducing the corrosion of HF on the positive electrode material; the synergistic modification of Te / Nb works together to inhibit the formation of lithium carbonate by lithium ions migrating on the surface of the positive electrode material and carbonate ions on the surface of the material, and the surface structure formed by the two can better resist the corrosion of the electrolyte, inhibit the occurrence of side reactions, solve the technical problem of battery flatulence, and improve the safety and stability of the battery.
[0034] Te / Nb co-doped and carbon nitride-coated positive electrode materials are obtained by carbon nitride coating. The synergistic modification of Te / Nb co-doping and carbon nitride coating can improve the thermal conductivity of the material, so that heat can be dissipated more quickly. At the same time, the surface activity of the material is reduced, the volume change of the positive electrode material is inhibited, and the occurrence of thermal runaway can be effectively inhibited, thereby improving the safety performance of the battery.
[0035] The present invention also discloses a method for preparing a tellurium and niobium doped and carbon nitride coated positive electrode material, wherein a precursor is prepared by a Te / Nb co-doping method, and the precursor is sintered with a lithium salt to obtain a Te / Nb co-doped positive electrode material, wherein Nb enters the lattice structure after doping, replaces the position of part of the transition metal ions, enhances the stability of the lattice, reduces the material damage caused by the change of the lattice structure during the charge and discharge process, and inhibits the occurrence of phase change, thereby improving the cycle stability of the positive electrode material, and after Te doping, the local electronic structure and chemical bond properties of the positive electrode material are changed, and a stronger chemical bond is formed with the surrounding atoms, thereby enhancing the structural stability of the material, and when Te and Nb are co-doped, Nb stabilizes the overall framework of the lattice, and Te further enhances the stability in the local structure, and the two are synergistically modified to stabilize the hexagonal α-Na The FeO2-type crystal structure reduces the volume change and phase change during the charge and discharge process, effectively inhibits the distortion and collapse of the lattice, and alleviates the local stress accumulation during the charge and discharge process of the particles, thereby maintaining the good mechanical stability and cycle performance of the material; the special structures of carbon nitride, such as the two-dimensional layered structure and porous structure, can provide additional transmission channels and adsorption sites for lithium ions, which helps lithium ions migrate faster under low temperature conditions; carbon nitride coating can improve the interfacial compatibility between the positive electrode material and the electrolyte, reduce the interfacial resistance, and make the transmission of lithium ions at the interface smoother; the carbon nitride coating can be used as a buffer layer to inhibit the volume change of the positive electrode material and maintain the structural stability of the material, so that during the low-temperature cycle, the positive electrode material can maintain good integrity and reduce the loss of active substances and performance degradation caused by volume change; carbon nitride coating can improve the electronic conductivity and ionic conductivity of the positive electrode material, which helps lithium ions migrate faster under low temperature conditions and improves the first coulombic efficiency, rate performance, and cycle performance of the battery at low temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The present invention provides a flow chart for preparing a positive electrode material doped with tellurium and niobium and coated with carbon nitride. DETAILED DESCRIPTION
[0037] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0038] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0039] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0040] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0041] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0042] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0043] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0044] like Figure 1 As shown, the present invention discloses a tellurium and niobium doped and carbon nitride coated positive electrode material and a preparation method thereof, and the specific steps are: weighing nickel salt, cobalt salt, manganese salt, tellurium salt and niobium salt according to a stoichiometric ratio, dissolving them in deionized water, and stirring to obtain a mixed solution A; adding a precipitant dropwise to the mixed solution A, adjusting the pH value, and filtering, washing, and vacuum drying the solution after the reaction to obtain a precursor; fully mixing the precursor with a lithium salt in a certain ratio and sintering them to obtain a tellurium and niobium doped positive electrode material; mixing the tellurium and niobium doped positive electrode material with a nitrogen-containing precursor in a mass ratio and sintering them to obtain a tellurium and niobium doped and carbon nitride coated positive electrode material.
[0045] The present invention discloses a tellurium and niobium doped and carbon nitride coated positive electrode material, the chemical formula of which is: LiNix Co y Mn 1-x-y-u-v Te u Nb v O2@C3N4, where 0.5 ≤ x ≤ 0.98, 0 < y < 0.5, 0 < u ≤ 0.1, 0 < v ≤ 0.1, and 1 - x - y - u - v > 0.
[0046] The technical solution of the present invention will be described in detail below through specific embodiments.
[0047] Example 1
[0048] The present invention discloses a preparation method of a positive electrode material doped with tellurium and niobium and coated with carbon nitride, comprising the following steps:
[0049] (1) Weigh 0.5 mol of nickel sulfate, 0.2 mol of cobalt sulfate, 0.2 mol of manganese sulfate, 0.05 mol of tellurium sulfate and 0.05 mol of sodium niobate, dissolve them in 500 ml of deionized water, stir at a speed of 350 revolutions per minute for 1 hour to obtain a mixed solution A.
[0050] (2) Slowly add ammonia water drop by drop to the mixed solution A, monitor the pH value of the solution using a pH meter, adjust the pH value to 10, the dropping speed is 1 ml / minute, the stirring speed is 450 revolutions per minute, stir and react for 4 hours, and keep the temperature at 28 °C during the stirring process.
[0051] (3) Filter the reacted solution by suction, wash the precipitate 3 times with deionized water and ethanol respectively to remove impurity ions, and then vacuum dry at 100 °C for 15 hours to obtain a precursor.
[0052] (4) Mix the precursor and lithium carbonate evenly according to the ratio of precursor: lithium salt = 1:1.04, place them in a crucible, put them into a firing furnace, under an air atmosphere, heat up to 920 °C at a heating rate of 9 °C / minute, keep warm for 10 hours, naturally cool to room temperature, crush and sieve to obtain the positive electrode material LiNi 0.5 Co 0.2 Mn 0.2 Te 0.05 Nb 0.05 O2;
[0053] (5) Mix the above positive electrode material doped with tellurium and niobium and melamine evenly according to the mass ratio of 100:2, place them in a crucible, put them into a firing furnace, under a nitrogen atmosphere, heat up to 550 °C at a heating rate of 5 °C / minute, keep warm for 4 hours, naturally cool to room temperature, crush and sieve to obtain the positive electrode material doped with tellurium and niobium and coated with carbon nitride LiNi 0.5 Co 0.2 Mn 0.2 Te0.05 Nb 0.05 O2@C3N4.
[0054] Example 2
[0055] The present invention discloses a method for preparing a tellurium and niobium doped and carbon nitride coated positive electrode material, comprising the following steps:
[0056] (1) Weigh 0.5 mol of nickel sulfate, 0.2 mol of cobalt sulfate, 0.1 mol of manganese sulfate, 0.1 mol of tellurium sulfate and 0.1 mol of sodium niobate, dissolve them in 500 ml of deionized water, stir at a speed of 380 rpm for 1.5 hours to obtain a mixed solution A.
[0057] (2) Ammonia water was added dropwise to the mixed solution A, and the pH value of the solution was monitored using a pH meter. The pH value was adjusted to 10, the dropping speed was 1.2 ml / min, the stirring speed was 480 rpm, and the reaction was stirred for 4.5 hours. The temperature was maintained at 29° C. during the stirring process.
[0058] (3) The solution after the reaction was filtered, and the precipitate was washed three times with deionized water and ethanol respectively to remove impurity ions, and then vacuum dried at 80° C. for 12 hours to obtain a precursor.
[0059] (4) The precursor and lithium carbonate are mixed evenly in a ratio of precursor: lithium salt = 1:1.05, placed in a sagger, placed in a sintering furnace, heated to 950°C at a heating rate of 10°C / min in an air atmosphere, kept warm for 8 hours, naturally cooled to room temperature, crushed, and sieved to obtain a tellurium and niobium doped positive electrode material LiNi 0.5 Co 0.2 Mn 0.1 Te 0.1 Nb 0.1 O2;
[0060] (5) The tellurium and niobium doped positive electrode material and melamine are mixed uniformly at a mass ratio of 100:1, placed in a sagger, placed in a sintering furnace, heated to 600°C at a heating rate of 5°C / min in a nitrogen atmosphere, kept warm for 2 hours, naturally cooled to room temperature, crushed, and sieved to obtain a tellurium and niobium doped and carbon nitride coated positive electrode material LiNi 0.5 Co 0.2 Mn 0.1 Te 0.1 Nb 0.1 O2@C3N4.
[0061] Example 3
[0062] The present invention discloses a method for preparing a tellurium and niobium doped and carbon nitride coated positive electrode material, comprising the following steps:
[0063] (1) Weigh 0.6 mol of nickel nitrate, 0.1 mol of cobalt nitrate, 0.2 mol of manganese nitrate, 0.05 mol of sodium tellurite and 0.05 mol of niobium oxalate, dissolve them in 500 ml of deionized water, stir at 400 rpm for 1.5 hours to obtain a mixed solution A.
[0064] (2) Add sodium hydroxide as a precipitant dropwise to the mixed solution A, monitor the pH value of the solution using a pH meter, adjust the pH value to 10.5, add at a rate of 1.5 ml / min, stir at a speed of 500 rpm, stir and react for 4.5 hours, and keep the temperature at 30° C. during stirring.
[0065] (3) The solution after the reaction was filtered, and the precipitate was washed 4 times with deionized water and ethanol respectively to remove impurity ions, and then vacuum dried at 110° C. for 18 hours to obtain a precursor.
[0066] (4) The precursor and lithium carbonate are mixed evenly in a ratio of precursor: lithium salt = 1:1.05, placed in a sagger, placed in a sintering furnace, heated to 900°C at a heating rate of 8°C / min in an air atmosphere, kept warm for 12 hours, naturally cooled to room temperature, crushed, and sieved to obtain a tellurium and niobium doped positive electrode material LiNi 0.6 Co 0.1 Mn 0.2 Te 0.05 Nb 0.05 O2;
[0067] (5) The tellurium and niobium doped positive electrode material and urea are mixed uniformly at a mass ratio of 100:4, placed in a sagger, placed in a sintering furnace, heated to 500°C at a heating rate of 4°C / min under an argon atmosphere, kept warm for 4.5 hours, naturally cooled to room temperature, crushed, and sieved to obtain a tellurium and niobium doped and carbon nitride coated positive electrode material LiNi 0.6 Co 0.1 Mn 0.2 Te 0.05 Nb 0.05 O2@C3N4.
[0068] Example 4
[0069] The present invention discloses a method for preparing a tellurium and niobium doped and carbon nitride coated positive electrode material, comprising the following steps:
[0070] (1) Weigh 0.8 mol of nickel carbonate, 0.1 mol of cobalt carbonate, 0.05 mol of manganese carbonate, 0.03 mol of tellurium chloride and 0.02 mol of sodium niobate, dissolve them in 500 ml of deionized water, and stir at a speed of 450 rpm for 2 hours to obtain a mixed solution A.
[0071] (2) Add sodium hydroxide as a precipitant dropwise to the mixed solution A, monitor the pH value of the solution using a pH meter, adjust the pH value to 11, add at a rate of 2 ml / min, stir at a speed of 550 rpm, stir and react for 5 hours, and maintain the temperature at 33° C. during stirring.
[0072] (3) The solution after the reaction was filtered, and the precipitate was washed 5 times with deionized water and ethanol respectively to remove impurity ions, and then vacuum dried at 120° C. for 20 hours to obtain a precursor.
[0073] (4) The precursor and lithium hydroxide are mixed evenly in a ratio of precursor: lithium salt = 1:1.06, placed in a sagger, placed in a sintering furnace, heated to 720°C at a heating rate of 7°C / min in an oxygen atmosphere, kept warm for 13 hours, naturally cooled to room temperature, crushed, and sieved to obtain a tellurium and niobium doped positive electrode material LiNi 0.8 Co 0.1 Mn 0.05 Te 0.03 Nb 0.02 O2;
[0074] (5) The tellurium and niobium doped positive electrode material and dicyandiamide are mixed uniformly at a mass ratio of 100:6, placed in a sagger, placed in a sintering furnace, heated to 450°C at a heating rate of 3°C / min in a helium atmosphere, kept warm for 5 hours, naturally cooled to room temperature, crushed, and sieved to obtain a tellurium and niobium doped and carbon nitride coated positive electrode material LiNi 0.8 Co 0.1 Mn 0.05 Te 0.03 Nb 0.02 O2@C3N4.
[0075] Example 5
[0076] The present invention discloses a method for preparing a tellurium and niobium doped and carbon nitride coated positive electrode material, comprising the following steps:
[0077] (1) Weigh 0.98 mol of nickel carbonate, 0.005 mol of cobalt carbonate, 0.005 mol of manganese carbonate, 0.005 mol of tellurium chloride and 0.005 mol of sodium niobate, dissolve them in 500 ml of deionized water, and stir at a speed of 500 rpm for 2 hours to obtain a mixed solution A.
[0078] (2) Add sodium hydroxide as a precipitant dropwise to the mixed solution A, monitor the pH value of the solution using a pH meter, adjust the pH value to 12, add at a rate of 2 ml / min, stir at a speed of 600 rpm, stir and react for 6 hours, and maintain the temperature at 35° C. during stirring.
[0079] (3) The solution after the reaction was filtered, and the precipitate was washed 5 times with deionized water and ethanol respectively to remove impurity ions, and then vacuum dried at 80° C. for 12 hours to obtain a precursor.
[0080] (4) The precursor and lithium hydroxide are mixed evenly in a ratio of precursor: lithium salt = 1:1.04, placed in a sagger, placed in a sintering furnace, heated to 600°C at a heating rate of 6°C / min in an oxygen atmosphere, kept warm for 16 hours, naturally cooled to room temperature, crushed, and sieved to obtain a tellurium and niobium doped positive electrode material LiNi 0.98 Co 0.005 Mn 0.005 Te 0.005 Nb 0.005 O2;
[0081] (5) The tellurium and niobium doped positive electrode material and dicyandiamide are mixed uniformly at a mass ratio of 100:10, placed in a sagger, placed in a sintering furnace, heated to 400°C at a heating rate of 3°C / min in a helium atmosphere, kept warm for 6 hours, naturally cooled to room temperature, crushed, and sieved to obtain a tellurium and niobium doped and carbon nitride coated positive electrode material LiNi 0.98 Co 0.005 Mn 0.005 Te 0.005 Nb 0.005 O2@C3N4.
[0082] Comparative Example 1
[0083] The ternary precursor Ni 0.5 Co 0.2 Mn 0.3 (OH)2 and lithium carbonate are mixed in a lithium ratio of 1:1.04, and added to a high-speed mixer for thorough mixing, with a mixing frequency of 30-50Hz and a mixing time of 20-40min to obtain a raw material mixture; the mixed material is sintered in an air atmosphere, directly from room temperature to 800-930℃, kept warm for 10-15 hours, cooled to room temperature, the powder is taken out, crushed, and passed through a 400-mesh sieve to obtain a sintered product; the sintered product is dry-mixed, and sintered twice in an air atmosphere at a sintering temperature of 600-850℃ for a constant temperature sintering time of 5-10h, and after cooling to room temperature, the undoped and uncoated positive electrode material LiNi is obtained after passing through a 400-mesh sieve. 0.5 Co 0.2 Mn 0.3 .
[0084] Comparative Example 2
[0085] The ternary precursor Ni 0.6 Co 0.1 Mn 0.3(OH)2 and lithium carbonate are mixed in a lithium ratio of 1:1.05, and added to a high-speed mixer for thorough mixing, with a mixing frequency of 30-50Hz and a mixing time of 20-40min to obtain a raw material mixture; the mixed material is sintered in an air atmosphere, directly from room temperature to 800-920℃, kept warm for 10-15 hours, cooled to room temperature, the powder is taken out, crushed, and passed through a 400-mesh sieve to obtain a sintered product; the sintered product is dry-mixed, sintered at a sintering temperature of 600-800℃ in an air atmosphere for a second sintering, and the constant temperature sintering time is 5-10h. After cooling to room temperature, the powder is passed through a 400-mesh sieve to obtain an undoped and uncoated positive electrode material LiNi 0.6 Co 0.1 Mn 0.3 .
[0086] Comparative Example 3
[0087] The ternary precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2 and lithium hydroxide are mixed in a lithium ratio of 1:1.06, and added to a high-speed mixer for thorough mixing, with a mixing frequency of 30-50Hz and a mixing time of 50-100min to obtain a raw material mixture; the mixed material is sintered in an oxygen atmosphere, directly from room temperature to 600-750℃, kept warm for 10-15 hours, cooled to room temperature, the powder is taken out, crushed, and passed through a 400-mesh sieve to obtain a sintered product; the sintered product is dry-mixed, and sintered twice in an oxygen atmosphere at a sintering temperature of 200-500℃ for a constant temperature sintering time of 5-10h, and after cooling to room temperature, the undoped and uncoated positive electrode material LiNi is obtained. 0.8 Co 0.1 Mn 0.1 .
[0088] Comparative Example 4
[0089] The ternary precursor Ni 0.98 Co 0.005 Mn 0.015 (OH)2 and lithium hydroxide are mixed in a lithium ratio of 1:1.04, and added to a high-speed mixer for thorough mixing, with a mixing frequency of 25-40Hz and a mixing time of 40-80min to obtain a raw material mixture; the mixed material is sintered in an oxygen atmosphere, directly from room temperature to 500-600℃, kept warm for 10-15 hours, cooled to room temperature, the powder is taken out, crushed, and passed through a 400-mesh sieve to obtain a sintered product; the sintered product is dry-mixed, and sintered twice in an oxygen atmosphere at a sintering temperature of 200-400℃ for a constant temperature sintering time of 6-10h, and after cooling to room temperature, the undoped and uncoated positive electrode material LiNi is obtained. 0.98 Co0.005 Mn 0.015 .
[0090] The materials obtained in Examples 1-5 and Comparative Examples 1-4 were subjected to 2025 button battery production tests. The test temperatures were 0°C and 25°C, the test voltage conditions were (3.0-4.3V), the rate performance test conditions were: 0.1C, 0.5C, 1C, 2C, 3C, two cycles of charge and discharge respectively, the rate performance calculation method was: 3C discharge capacity / 0.1C discharge capacity, and the test results are shown in the following table.
[0091] Table 1: 0.1C first discharge efficiency, rate performance and cycle performance of comparative examples and example samples at 25°C
[0092]
[0093]
[0094] Table 2: 0.1C first discharge efficiency, rate performance and cycle performance of comparative examples and example samples at 0°C
[0095]
[0096] A tellurium and niobium doped and carbon nitride-coated positive electrode material prepared by the present invention is first doped with tellurium and niobium into a precursor, which is then mixed with a lithium salt, sintered, crushed, and sieved to obtain a tellurium and niobium doped positive electrode material, and finally the tellurium and niobium doped positive electrode material is mixed with a nitrogen-containing precursor, sintered, crushed, and sieved to obtain a tellurium and niobium doped and carbon nitride-coated positive electrode material. It can be seen from the embodiments and comparative examples in Tables 1 and 2 that the tellurium and niobium doped and carbon nitride-coated positive electrode material provided by the present invention has significantly superior first efficiency, rate and cycle performance, and also exhibits excellent electrochemical performance at low temperatures.
[0097] This method adopts Te / Nb co-doping, and the two are synergistically modified to stabilize the crystal structure of the material, maintain the good mechanical stability and cycle performance of the material, effectively enhance the electronic conductivity and ion diffusion rate, and can meet the needs of fast charging and high-current discharge. At the same time, it inhibits the lithium ions migrating on the surface of the positive electrode material from forming lithium carbonate with the carbonate ions on the surface of the material, solving the technical problem of battery flatulence; the synergistic modification of Te / Nb co-doping and carbon nitride coating can improve the thermal conductivity of the material, effectively inhibit the occurrence of thermal runaway, and improve the safety performance of the battery; carbon nitride coating can provide additional transmission channels and adsorption sites for lithium ions, which helps lithium ions migrate faster under low temperature conditions, thereby improving the first coulombic efficiency, rate and cycle performance of the battery at low temperatures.
[0098] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A tellurium and niobium doped and carbon nitride coated positive electrode material, characterized in that: Chemical formula: LiNi x Co y Mn 1-x-y-u-v Te u Nb v O2@C3N4; Among them, 0.5 ≤ x ≤ 0.98, 0 < y < 0.5, 0 < u ≤ 0.1, 0 < v ≤ 0.1, and 1 - x - y - u - v > 0.
2. The tellurium and niobium doped and carbon nitride coated positive electrode material according to claim 1, characterized in that: The tellurium and niobium doped and carbon nitride coated cathode material includes a tellurium and niobium doped cathode material, and carbon nitride coated on the surface of the tellurium and niobium doped cathode material.
3. The method for preparing a tellurium and niobium doped and carbon nitride coated positive electrode material according to claim 1 or 2, characterized in that: It includes the following steps: Step 1: Weigh nickel salt, cobalt salt, manganese salt, tellurium salt and niobium salt according to the stoichiometric ratio in the chemical formula, dissolve them in deionized water, mix and stir to obtain a mixed solution A; Step 2: Add a precipitant to the mixed solution A, adjust the pH value of the solution to alkaline, stir and react to obtain a mixed solution B; Step 3: Filter the mixed solution B by suction, wash the precipitate, and then vacuum dry at 80 - 120 °C for 12 - 24 hours to obtain a precursor; Step 4: Mix the precursor with lithium salt充分, heat up to 600 - 950 °C, keep warm for 8 - 16 hours, naturally cool to room temperature, crush and sieve to obtain a tellurium and niobium doped cathode material; Step 5: Mix the tellurium and niobium doped cathode material with a nitrogen-containing precursor evenly, under an inert atmosphere, heat up to 400 - 600 °C, keep warm for 2 - 6 hours, naturally cool to room temperature, crush and sieve to obtain a tellurium and niobium doped and carbon nitride coated cathode material.
4. The method for preparing a tellurium and niobium doped and carbon nitride coated positive electrode material according to claim 3, characterized in that: In Step 1, the rotation speed is controlled at 300 - 500 revolutions per minute; The nickel salt is one or more of nickel sulfate, nickel chloride, nickel carbonate, nickel nitrate; The cobalt salt is one or more of cobalt sulfate, cobalt chloride, cobalt carbonate, cobalt nitrate; The manganese salt is one or more of manganese sulfate, manganese chloride, manganese carbonate, manganese nitrate; The tellurium salt is one or more of tellurium sulfate, tellurium chloride, sodium tellurate; The niobium salt is one or more of sodium niobate, niobium oxalate, niobium hydroxide.
5. The method for preparing a tellurium and niobium doped and carbon nitride coated positive electrode material according to claim 3, characterized in that: In Step 2, the precipitant includes one or more of ammonia water, sodium hydroxide, sodium carbonate; The pH value is adjusted to 9 - 12, and the dropping speed of the precipitant is controlled at 1 - 2 milliliters per minute; The stirring speed is 400 - 600 revolutions per minute, stir and react for 2 - 6 hours, and keep the temperature at 25 - 35 °C during the stirring process.
6. The method for preparing a tellurium and niobium doped and carbon nitride coated positive electrode material according to claim 3, characterized in that: In Step 4, the lithium salt is lithium carbonate or / and lithium hydroxide; Under an air or oxygen atmosphere, heat up to 600 - 950 °C at a heating rate of 5 - 10 °C per minute.
7. The method for preparing a tellurium and niobium doped and carbon nitride coated positive electrode material according to claim 3, characterized in that: In Step 4, the mass ratio of the precursor to the lithium salt is 1:(1.04 - 1.06).
8. The method for preparing a tellurium and niobium doped and carbon nitride coated positive electrode material according to claim 3, characterized in that: In Step 5, the mass ratio of the tellurium and niobium doped cathode material to the nitrogen-containing precursor is 100:(1 - 10).
9. The method for preparing a tellurium and niobium doped and carbon nitride coated positive electrode material according to claim 3, characterized in that: In Step 5, the nitrogen-containing precursor is one or more of melamine, urea, dicyandiamide; 10. The method for preparing a tellurium and niobium doped and carbon nitride coated positive electrode material according to claim 3, characterized in that: In Step 5, the inert atmosphere includes one or more of nitrogen, argon, helium; Heat up to 400 - 600 °C at a heating rate of 2 - 5 °C per minute.
Citation Information
Cited By
Modified high-nickel ternary positive electrode material as well as preparation method and application thereof
CN120261520A
Modified high-nickel ternary positive electrode material, preparation method and application thereof
CN120261520B
Oxide-coated ion-doped sodium ferric sulfate positive electrode material as well as preparation method and application thereof
CN120978045A
Outdoor low-temperature sodium ion battery and preparation method thereof
CN121726493A
Outdoor low-temperature sodium-ion battery and preparation method thereof
CN121726493B
